2018
DOI: 10.1016/j.energy.2018.09.078
|View full text |Cite
|
Sign up to set email alerts
|

Do renters skimp on energy efficiency during economic recessions? Evidence from Northeast Scotland

Abstract: This paper investigates tenants' willingness to pay (WTP) for energy efficiency in the private rented housing sector. Using data from Aberdeen city and Shire in Scotland between the third quarter of 2013 and the second quarter of 2017, rent premiums of 2-11% associated with more energy efficient dwellings are found, and the magnitudes of these premiums are considerable compared to those of other physical attributes. Such premiums however, are significantly reduced during economic recession, suggesting that ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…It is important to note, that financial incentives and grants and their impact on WTP for energy efficiency improvement measures in households were examined in details by most studies dealing with WTP for energy renovation [61,138,140,143,145], however these studies revealed contradictory results especially in terms of the impacts of subsidies and loans on WTP for energy efficiency improvements in households. The size of the acceptable price premium, that potential homebuyers are willing to pay for green buildings, is likely to be affected negatively by short-term financial incentives proposed by the government.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note, that financial incentives and grants and their impact on WTP for energy efficiency improvement measures in households were examined in details by most studies dealing with WTP for energy renovation [61,138,140,143,145], however these studies revealed contradictory results especially in terms of the impacts of subsidies and loans on WTP for energy efficiency improvements in households. The size of the acceptable price premium, that potential homebuyers are willing to pay for green buildings, is likely to be affected negatively by short-term financial incentives proposed by the government.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Liu et al [138] investigated WTP during economic recessions for energy efficiency in the private rented housing sector. Results showed, that respondents are saving energy costs by different ways (such as heating one room rather than the whole property; or wearing more layers of clothing) rather than paying a premium for energy efficiency.…”
Section: Wtp For Energy Efficiency Improvements In Householdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoffman and Henn (2008) [39] and Yau (2012) [40] demonstrate that consumers are affected by several factors when deciding to move into energy-efficient buildings, such as economic or/and psychological reasons. Encinas et al (2018) [42] and Liu et al (2018) [43] investigate the consumers' willingness to pay for energy efficient buildings, and both conclude that people tend to pay more for higher level of energy efficient buildings. Chau et al (2010) [20] apply discrete choice experiments to identify the factors affecting the preference for energy-efficient buildings in Hong Kong.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several methods to gather the stated preference data. One of approaches is contingent valuation method (CVM), which is directly asking the consumers their willingness to pay [42,44]. Although the CVM is a simple and easy to conduct, it presents a weakness by suggesting the existence of either overestimate or underestimate of the true values.…”
Section: The Design Of the Discrete Choice Experimentsmentioning
confidence: 99%